Behavioral effects of triazolam and pregnanolone combinations: reinforcing and sedative-motor effects in female rhesus monkeys - Cook, Jemma E.; Platt, Donna M.; Rüedi-Bettschen, Daniela; Rowlett, James K. (Frontiers in Psychiatry, 2023)
Benzodiazepines (BZs) are prescribed as anxiolytics, but their use is limited by side effects including abuse liability and daytime drowsiness. Neuroactive steroids are compounds that, like BZs, modulate the effects of GABA at the GABAA receptor. In a previous study, combinations of the BZ triazolam and neuroactive steroid pregnanolone produced supra-additive (i.e., greater than expected effects based on the drugs alone) anxiolytic effects but infra-additive (i.e., lower than expected effects based on the drugs alone) reinforcing effects in male rhesus monkeys, suggestive of an improved therapeutic window. In the present study, four female rhesus monkeys self-administered triazolam, pregnanolone, and triazolam-pregnanolone combinations intravenously under a progressive-ratio schedule. In contrast to our previous study with males, triazolam-pregnanolone combinations had primarily supra-additive reinforcing effects in three monkeys but infra-additive reinforcing effects in one monkey. In order to assess characteristic sedative-motor effects of BZ-neuroactive steroid combinations, four female rhesus monkeys were administered triazolam, pregnanolone, and triazolam-pregnanolone combinations. Trained observers, blinded to condition, scored the occurrence of species-typical and drug-induced behaviors. Scores for deep sedation (i.e., defined as atypical loose-limbed posture, eyes closed, does not respond to external stimuli) and observable ataxia (any slip, trip, fall, or loss of balance) were significantly increased by both triazolam and pregnanolone. When combined, triazolam-pregnanolone combinations had supra-additive effects for inducing deep sedation, whereas observable ataxia was attenuated, likely due to the occurrence of robust sedative effects. These results suggest that significant sex differences exist in self-administration of BZ-neuroactive steroid combinations, with females likely to show enhanced sensitivity to reinforcing effects compared with males. Moreover, supra-additive sedative effects occurred for females, demonstrating a higher likelihood of this adverse effect when these drug classes are combined.